Development of HICAH Learning Media (Count Fractions) for Blind Students in Makassar - HN, Wahyudi; Al-Usrah, Muzayyinah; Dewa, Yoga Indar (Department of Special Education, 2023)
This study aims to determine the feasibility of the media, student responses, and teacher responses to Hicah learning media (count fractions) for blind students in Makassar. This research is development research using the ADDIE model (Analysis, Design, Development, Implementation, dan Evaluation). The analysis stage is used to find out about the problems and needs of students, the design stage makes media prototypes according to student needs, then the development is carried out media validation, implementation as a media trial, and evaluation by revising to adjust the results of field trials. The results of this study are: (1) The results of the validation of the Hicah learning media developed are feasible to use and feasible to be tested on students and teachers with a media feasibility weight of 90% percent. (2) The responses of the blind students of SLB Negeri 1 Makassar, SLB-A YAPTI Makassar, and SLB Yukartuni to the Hicah learning media developed received a positive response. Student responses strongly agree by 83 percent. (3) The responses of mathematics teachers and class teachers at SLB Negeri 1 Makassar, SLB-A YAPTI Makassar, and SLB Yukartuni to the Hicah learning media developed were given a very good response. The positive response of the teacher can be seen from the percentage of 100 percent positive response.